Development and validation of a reversed-phase column liquid chromatographic method for simultaneous determination of two novel gliptins in their binary mixtures with Metformin - Mohammad, Mohammad Abdul-Azim; Elkady, Ehab Farouk; Fouad, Marwa Ahmed (European Journal of Chemistry, 2012)
A new, simple, accurate, and precise liquid chromatographic method has been developed and validated for the determination of two novel dipeptidylpeptidase-4 (DPP-4) inhibitors; namely vildagliptin (VLG) and saxagliptin HCl (SXG) simultaneously in their binary mixtures with metformin HCl (MET). Chromatographic separation was achieved on an Inertsil® CN-3 column (250 mm x 4.6 mm, 5 µm). Isocratic elution using a mobile phase of potassium dihydrogen phosphate buffer pH (4.6) - acetonitrile (15:85, v:v) at a flow rate of 1 mL/min with UV detection at 208 nm was performed. The liquid chromatographic method was used for the simultaneous determination of either VLG, SXG and MET in the range of 5-200, 0.5-20 and 50-2000 μg/mL, respectively. The methods developed were satisfactorily applied to the analysis of the pharmaceutical formulations and proved to be specific and accurate for the quality control of the cited drugs in pharmaceutical dosage forms.